Improvement of Soil Fertility and Rice Productivity with Use of Coal Derived Humic Acid and Mineral Fertilization under Inceptisol of Varanasi, India - Kumar, Dileep; Singh, A. P.; Meena, V. S. (International Journal of Bio-resource and Stress Management, 2017)
Use of organic and inorganic fertilizers in balanced and integrated manner may enhance the accumulation of soil organic matter and improves soil physical properties. A two year replicated pot experiment was conducted to assess the influence of coal derived potassium humate (PH) and mineral fertilizers. The experiment followed a completely randomized 2×3×2×3 factorial design comprising two fertility levels (75 and 100% NPK), three doses of PH (0; 5.0; and 10.0 mg kg-1), two doses of zinc sulphate (0; and 12.5 mg kg-1). Results showed significant enhancement in rice grain yield as well as availability of nutrients with sole and combined application of 10 mg kg-1 PH with 100% NPK and 12.5 mg kg-1 zinc sulphate as compared to 75 and 100% of NPK alone. Meanwhile, use of PH10 showed 35% higher grain yield compared without PH0 application, it was 19% higher as compared to PH5. Significant interaction effect of different levels of PH with NPK and zinc was observed in grain yield. Application of 100% NPK with 10 mg kg-1 PH significantly enhances nutrient availability as compared to control treatment after rice harvest. These results suggested that the used of PH and mineral fertilization in integrated manner enhance the crop productivity as well as soil fertility of rice system in the alluvial soil under Indo-Gangetic Plain of India.